in Theory of Computation edited by
875 views
2 votes
2 votes

How to convert given finite state automaton into regular expression.

in Theory of Computation edited by
875 views

4 Comments

when you will remove q1, then loop 'xy' will be added on q0 as well as transition 'xy' will be added from q0->q2
1
1

let we have removed q1 then what is the all transitions which may be lost....

1. q0->q1->q0     xy    (it could be represented as self loop on q0)

2.q0->q1->q2      xy    (it could be obtained by taking transition from qo->q2 as xy)

1
1
I didn't knew how to handle this case. Thank you very much :)
0
0

2 Answers

0 votes
0 votes
"  (X+Y)*X (Y(X+Y)X)* (X+Y) (Y+Z)   "  i got this RE
0 votes
0 votes
(yz+(x+z))*(y+y+z)

1 comment

Plz explain it with state elimination method
0
0

Related questions